2006
DOI: 10.1002/uog.3735
|View full text |Cite
|
Sign up to set email alerts
|

P15.11: Subsequent pregnancy outcome after embolisation of uterine arteriovenous malformation

Abstract: To identify if ultrasound measurement of endometrial thickness is predictor of retained products of conception in women with clinical suspicion of incomplete miscarriage. Methods: This was a prospective study of 100 women with a diagnosis of incomplete miscarriage who were referred for surgical evacuation. All women had a positive pregnancy test and ultrasound findings suggestive of retained product of conception. The indication for intervention was heavy vaginal bleeding or the endometrial thickness above 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In the systematic review of Peitsidis et al [10], 17 pregnancies were reported after uterine artery embolizations (17%). All pregnancies resulted in viable healthy neonates, except in one case in which total abdominal hysterectomy was performed in a uterus at 7.4 weeks of gestation due to uncontrolled heavy bleeding [27]. The mean time of delay from treatment to subsequent pregnancy was 15.7 ± 11.7 months with range (2 to 36) months.…”
Section: Discussionmentioning
confidence: 99%
“…In the systematic review of Peitsidis et al [10], 17 pregnancies were reported after uterine artery embolizations (17%). All pregnancies resulted in viable healthy neonates, except in one case in which total abdominal hysterectomy was performed in a uterus at 7.4 weeks of gestation due to uncontrolled heavy bleeding [27]. The mean time of delay from treatment to subsequent pregnancy was 15.7 ± 11.7 months with range (2 to 36) months.…”
Section: Discussionmentioning
confidence: 99%